Injection syringe designed as surgical tools in resource-limited settings. (July 2021) - Sarkar, Sucheta; Barai, Bhaskar; Sengupta, Ritankar; De, Utpal
Surgical innovations have a long tradition and are fundamental to the future of surgery. Practical application of an idea is its essence. It is the surgeon's responsibility to discover, translate and propagate such ideas to reduce surgical costs for the economically downtrodden. Our article addresses one aspect of this.